Arts-Based Methods for Decolonising Participatory Research - Seppälä, Tiina; Sarantou, Melanie; Miettinen, Satu (Routledge Advances in Art and Visual Studies, 2021)
In an effort to challenge the ways in which colonial power relations and Eurocentric knowledges are reproduced in participatory research, this book explores whether and how it is possible to use arts-based methods for creating more horizontal and democratic research practices. In discussing both the transformative potential and limitations of arts-based methods, the book asks: What can arts-based methods contribute to decolonising participatory research and its processes and practices? The book takes part in ongoing debates related to the need to decolonise research, and investigates practical contributions of arts-based methods in the practice-led research domain. Further, it discusses the role of artistic research in depth, locating it in a decolonising context. The book will be of interest to scholars working in art history, design, fine arts, service design, social sciences and development studies.